2013
DOI: 10.1007/s00198-013-2513-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific hip fracture risk in community-dwelling and institutionalized seniors age 65 years and older

Abstract: We confirm for seniors living in the community that women have a higher risk of hip fracture than men. However, among institutionalized seniors, men are at higher risk for hip fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 72 publications
1
17
0
1
Order By: Relevance
“…ese results are in line with those of previous studies [21,22]. Although diabetes was associated with significantly increased risk of hip fracture, a previous meta-analysis reported that the risk of hip fractures is more pronounced in men with diabetes [10].…”
Section: Discussionsupporting
confidence: 92%
“…ese results are in line with those of previous studies [21,22]. Although diabetes was associated with significantly increased risk of hip fracture, a previous meta-analysis reported that the risk of hip fractures is more pronounced in men with diabetes [10].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, this patient group benefitted greatly from CGA with regard to mortality. Community-dwelling hip fracture patients are generally younger and fitter 29 and therefore may have a better prognosis regardless of the geriatrician’s input. Patients living in long-term residential care are generally in worse health and are thus more likely to have a poorer outcome, 30 and the geriatricians’ principal role is to ensure quality of care toward the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbid conditions, such as hemiplegia and dementia in individuals of an advanced age, and the degree of independence in daily life activities, as well as height, weight, and BMI, are reported to be factors associated with falls and fractures. 2 , 27 , 28 In our study, examinations of the systemic diseases frequently seen among the elderly population revealed that dementia was more frequent and that the kyphosis angle was wider in nursing home patients with dementia than in individuals with dementia who reside in non-nursing home settings.…”
Section: Discussionmentioning
confidence: 45%
“…The fact that the fracture incidence rate increases with age is well known; however, the effect of age on the fracture rate among nursing home residents is not clear. 27 In addition to studies that have established the effects of age on fracture risk, 2 , 27 , 28 there are studies that claim it has no effect. 29 , 30 In our study, the number of vertebral fractures was demonstrated to be positively correlated with age in both groups.…”
Section: Discussionmentioning
confidence: 99%